Table_1_Soil CO2 and N2O emissions and microbial abundances altered by temperature rise and nitrogen addition in active-layer soils of permafrost peatland.DOCX - Yanyu Song; Xiaofeng Cheng; Changchun Song; Mengting Li; Siqi Gao; Zhendi Liu; Jinli Gao; Xianwei Wang (2022)
Changes in soil CO 2 and N 2 O emissions due to climate change and nitrogen input will result in increased levels of atmospheric CO 2 and N 2 O, thereby feeding back into Earth’s climate. Understanding the responses of soil carbon and nitrogen emissions mediated by microbe from permafrost peatland to temperature rising is important for modeling the regional carbon and nitrogen balance. This study conducted a laboratory incubation experiment at 15 and 20°C to observe the impact of increasing temperature on soil CO 2 and N 2 O emissions and soil microbial abundances in permafrost peatland. An NH 4 NO 3 solution was added to soil at a concentration of 50 mg N kg −1 to investigate the effect of nitrogen addition. The results indicated that elevated temperature, available nitrogen, and their combined effects significantly increased CO 2 and N 2 O emissions in permafrost peatland. However, the temperature sensitivities of soil CO 2 and N 2 O emissions were not affected by nitrogen addition. Warming significantly increased the abundances of methanogens, methanotrophs, and nirK-type denitrifiers, and the contents of soil dissolved organic carbon (DOC) and ammonia nitrogen, whereas nirS-type denitrifiers, β-1,4-glucosidase (βG), cellobiohydrolase (CBH), and acid phosphatase (AP) activities significantly decreased. Nitrogen addition significantly increased soil nirS-type denitrifiers abundances, β-1,4-N- acetylglucosaminidase (NAG) activities, and ammonia nitrogen and nitrate nitrogen contents, but significantly reduced bacterial, methanogen abundances, CBH, and AP activities. A rising temperature and nitrogen addition had synergistic effects on soil fungal and methanotroph abundances, NAG activities, and DOC and DON contents. Soil CO 2 emissions showed a significantly positive correlation with soil fungal abundances, NAG activities, and ammonia nitrogen and nitrate nitrogen contents. Soil N 2 O emissions showed positive correlations with soil fungal, methanotroph, and nirK-type denitrifiers abundances, and DOC, ammonia ...